Baseline measures of Primary Health Care Team functioning and overall Primary Health Care performance at Du Noon Community Health Centre - Mukiapini, Shapi (Department of Public Health and Family Medicine, 2017)
Background: The importance of effective team work for improving quality of care has been demonstrated consistently in research. We conducted a baseline measure of team effectiveness and a baseline measure of primary health care performance. Aim: To improve Primary health care team effectiveness and ultimately the quality and user experience of primary care at Du Noon Community Health Centre. (CHC) Setting: Du Noon CHC in the southern/western substructure of the Cape Town Metro district services. Methods: A cross sectional study using a combination of Nominal Group Technique (NGT) method and a questionnaire survey to assess PHC team effectiveness and to obtain baseline measure for Primary Health Care (PHC) organization and performance. Results: Data from 20 providers from the primary health care team, showed that the PHC team members perceived their team as a well functioning team (70% agreement on the 7 items of the PHC team assessment tool, incorporated in the ZA PCAT. The NGT method reveals that communication and leadership are the main challenges to effective team functioning, The NGT also provides ideas on how to deal with these challenges. Data from 110 users and 12 providers using the ZA PCAT: 18.2% of users rated first contact-access as acceptable to good; 47,3% rated ongoing care as acceptable to good. The remaining subdomains of the ZA PCAT were rated as acceptable to good by at least 65% of the users. 33% of the providers (doctors and clinical nurse practitioners) rated first contact-access as acceptable to good; 25% rated ongoing care as acceptable to good, the remaining subdomains of the ZA PCAT were rated as acceptable to good by at least 50% of providers. First contact-access received the lowest acceptable to good score (18.2%) and comprehensiveness (service available) received the highest score (88.2%) from the users. For the providers the lowest acceptable to good score was for ongoing care (25%) and the highest acceptable to good score was for primary health care team (100%). The total primary scores are good (above 60%) for both users and providers but moderately higher for the providers. Conclusions: How teams perceive their effectiveness can motivate them to generate ideas for improvement. There were discrepancies between ZA PCAT (PHC team functioning) results and the NGT method results. The ZA PCAT (8 pre-existing domains) baseline results show a contrast between providers' and users' perceptions of the PHC system at Du Noon consistent with the finding of the Western Cape ZA PCAT study. We encourage Du Noon CHC to use these results to improve the user experience of primary health care services there.